Experimental study of strain rate effects on normal weight concrete after exposure to elevated temperature - Zhai, C.; Chen, L.; Fang, Q.; Chen, Wensu; Jiang, X. (Kluwer Academic Publishers, 2017)
© 2016, RILEM. The effects of strain rate ranging from 10-4 to 300 s-1 on normal weight concrete after exposure to elevated temperature up to 1000 °C were experimentally investigated using a servo-hydraulic testing machine and a split Hopkinson pressure bar. The casted cylinder concrete specimens were firstly heated in a microwave oven, and then cooled down to the ambient temperature with control. Experimental results proved that the normal weight concrete after high temperature exposure still showed significant strain rate dependency. The dynamic increase factor(DIF) for compressive strength decreased with the exposed elevated temperature from 600 to 800 °C, and increased from 800 to 1000 °C. The DIF of concrete after exposure to elevated temperature is smaller than that at the ambient temperature according to CEB code. The larger the compressive strength is, the smaller the DIF of normal weight concrete after high temperature exposure will be. In addition, further comparison showed that the DIF after high temperature exposure is larger than that exactly at the same high temperature. An empirical model of DIF for normal weight concrete after elevated temperature exposure was proposed based on the experimental data. It obviously benefits the assessment of blast resistant capacity of post-fired concrete structures, as well as referred retrofitting techniques.